2012
DOI: 10.1016/j.jaci.2012.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Imidazoquinoline Toll-like receptor 8 agonists activate human newborn monocytes and dendritic cells through adenosine-refractory and caspase-1–dependent pathways

Abstract: Background Newborns suffer frequent infection and manifest impaired vaccine responses, motivating a search for neonatal vaccine adjuvants. Alum is a neonatal adjuvant, but may confer a Th2 bias. Toll-like receptor (TLR) agonists are candidate adjuvants, but human neonatal cord blood monocytes (Mos) demonstrate impaired Th1-polarizing responses to many TLR agonists due to plasma adenosine acting via cAMP. TLR8 agonists, including imidazoquinolines (IMQs) such as the small synthetic 3M-002, induce adult-level TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
133
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(146 citation statements)
references
References 59 publications
11
133
2
Order By: Relevance
“…As mycobacteria infect not only monocytes/macrophages but also dendritic cells (DC), we tested both monocytes/macrophages and myeloid DC (mDC) for their ability to produce cytokines in response to Toll-like receptor (TLR) ligation. Although mycobacteria are not known to signal through Toll-like receptor 7 (TLR7) or TLR8, we chose the TLR7/8 agonist R848 because monocytes/macrophages and myeloid dendritic cells from infants show reduced function compared to those from adults, and R848 has been demonstrated to potently activate infant cell populations (33,34). At 16 to 18 weeks after vaccination, in vitro R848 stimulation of PBMC resulted in higher frequencies of interleukin 12 (IL-12)-producing monocytes/macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As mycobacteria infect not only monocytes/macrophages but also dendritic cells (DC), we tested both monocytes/macrophages and myeloid DC (mDC) for their ability to produce cytokines in response to Toll-like receptor (TLR) ligation. Although mycobacteria are not known to signal through Toll-like receptor 7 (TLR7) or TLR8, we chose the TLR7/8 agonist R848 because monocytes/macrophages and myeloid dendritic cells from infants show reduced function compared to those from adults, and R848 has been demonstrated to potently activate infant cell populations (33,34). At 16 to 18 weeks after vaccination, in vitro R848 stimulation of PBMC resulted in higher frequencies of interleukin 12 (IL-12)-producing monocytes/macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study using a polysaccharide microparticle adjuvant (Advax) also demonstrated protection against influenza virus challenge (31); likewise, an alphavirus-based adjuvant improved protection compared to antigen alone (32). It is of note that all these formulations are microparticle based, though it is not clear how the particles are being recognized by the immune system as studies have suggested that IL-1␤ responses in early life are deficient (33); however, this may be dependent upon the agonist used (34).…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, PRR activity in mononuclear cells increases until about 33 weeks of gestation, with the earliest activity detected in endosomal (TLR7, 8 and 9) and intracellular (e.g. NLRs), followed by extracellular PRRs such as the TLR1, 2, 4 and 5 and the dectin-1 receptor [9,16].…”
Section: Box 2 Relative Importance Of the Innate And Adaptive Immune mentioning
confidence: 99%